Fear Emotion of Reading the Horror Webtoon “Kemala” with Background Music - Ahmad Zulkifli; Hafiz Aziz Ahmad (Jurnal Minfo Polgan, 2024)
Technological innovations in webtoons, such as the capability of adding background music, change the comic reading experience and thus deserve further research. One of the comic titles that uses this feature is the well-known Indonesian horror comic, Kemala. Background music is known to be an important component in audio-visual media, especially in the horror genre. Indeed, it functions as a tool for eliciting emotions of fear that match the horror narrative. Essentially, the horror genre aims to scare its audience. Having an additional source of horror through the usage of background music might help horror webtoons achieve their goal. It is imperative to have specific research that examines the effect of background music on the emotion of fear in reading horror webtoons. This study, using the horror comic Kemala, conducted a two-group experimental approach: one group read the comic without music while another group read the comic with music to measure the differences in the emotion of fear using a questionnaire. Finally, a Mann-Whitney U Test was done using SPSS; it was found that there was a significant difference in fear levels between the groups. Thus, reading Kemala with background music provides a scarier reading experience.